Fault location in the distribution system with load profile based variation compensation - Orpilla, Michael B.
Accurate and fast location of fault is very crucial in the distribution system to ensure the continuity and quality of power supply. This research addressed the weaknesses of the previous impedance based fault location that neglect load variation and those that assumes uniform load variation compensation. It is done by performing load flow based on the representative load profile of each type of load. The proposed method is compared to existing fault location in three test cases including actual distribution feeder and it shows an improved fault location having 24Hr average relative error of less than 6 percent. The method is also robust amidst effect of line impedance, load model, unknown load increased and decreased. The method also is quite fast and could be used for online application providing result of about 25 seconds for a normal rural distribution feeder.